Synthesis, Structure and Chemical Vapour Deposition Studies on the Group 13 Complexes [Me2Mtfacnac] [M = Al, Ga, In; Htfacnac = F3CC(OH)CHC(CH3)NCH2CH2OCH3]. Issue 11 (18th March 2016) - Cosham, Samuel D.; Hamilton, Jeff A.; Hill, Michael S.; Johnson, Andrew L.; Molloy, Kieran C.
Abstract: A family of group 13 metal dimethyl complexes of the general formula [Me2 MMeC(O)CHC(NCH2 CH2 OMe)CF3 ] [M = Al (2 ), Ga (3 ) or In (4 )] was synthesised by reaction of the isolated free ligand1 with the corresponding trimethyl metal reagents. The isolated complexes2–4 were characterised by elemental analysis and NMR spectroscopy, and the molecular structures of the complexes were determined by single‐crystal X‐ray diffraction, which revealed them to be monomeric five‐coordinate complexes with coordination of the pendent ether‐bearing lariat in the solid state. Thermogravimetric analysis showed complexes2 –4 all to have residual masses at 200 °C of 2.4 % or less, well below the value for the respective metal oxides, and vapour pressure measurements showed the indium complex4 to be an order of magnitude less volatile (0.09 Torr at 80 °C) than the Al (2 ) and Ga (3 ) analogues, despite their being isoleptic systems. Complexes2 –4 were investigated for their utility in the low‐pressure metal organic chemical vapour deposition of the respective metal oxides in the absence of additional oxidant at 400 °C on silicon substrates. Abstract : Complexes [Me2 MMeC(O)CHC(NCH2 CH2 OMe)CF3 ] (M = Al, Ga, In) were synthesised and evaluated for their application in the CVD of metal oxide thin films. Although the In complex is an order of magnitude less volatile than the Al and Ga analogues, CVD of the In precursor in the absence of additional O2 oxidant produced highly orientated thin films of (222)‐oriented In2 O3 .